Androgen Deprivation Therapy Use Increases the Risk of Heart Failure in Patients With Prostate Cancer: A Population‐Based Cohort Study. (7th November 2018) - Kao, Hui‐Han; Kao, Li‐Ting; Li, I‐Hsun; Pan, Ke‐Ting; Shih, Jui‐Hu; Chou, Yu‐Ching; Wu, Sheng‐Tang
Abstract: The aim of this study was to investigate the relationship between androgen deprivation therapy and heart failure among prostate cancer patients. This cohort study used the data from the Taiwan Longitudinal Health Insurance Database 2005. In the full cohort study, we identified 1244 prostate cancer patients who had received androgen deprivation therapy as the study cohort and 1806 prostate cancer patients who did not receive androgen deprivation therapy as the comparison cohort. To eliminate potential bias, we performed a propensity score‐matched cohort study. Each prostate cancer patient was tracked for 1 year from the index date to ascertain whether they were subsequently diagnosed with heart failure. In the full cohort study, incidence rates of heart failure per 100 person‐years within the 1‐year follow‐up period were 4.00 (95%CI, 2.95‐5.30) and 1.89 (95%CI, 1.30‐2.66) for androgen deprivation therapy users and nonusers, respectively. In addition, the multivariable Cox regression indicated that the hazard ratio (HR) of heart failure among androgen deprivation therapy users was 1.72 (95%CI, 1.08‐2.73) compared with those androgen deprivation therapy nonusers. In the propensity score‐matched cohort study, the adjusted HR for heart failure among androgen deprivation therapy users was 1.92 (95%CI, 1.15‐3.18) compared with propensity score‐matched nonusers. In conclusion, this study found that androgen deprivation therapy users had a higher risk of heart failure than nonusers among prostate cancer patients in both the full cohort study and the propensity score‐matched study.